Жаростійкість різних садових груп і сортів троянд - Melnik, M.A.; Dubova, O.V.; Lyakh, V.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The results of studying the effect of high temperatures on the resistance to heat damage of leaf blade of six groups of garden roses and wild Rosa canina L. are presented. It is established that the lethal temperature for the leaves of garden roses is 60...65 °C. The most heat-resistant are Rosa canina and the majority of varieties of ground cover and climbing roses, the leaves of which endure very high temperatures.